Plantar pressure gait analysis in children with cerebral palsy - Raposo, Maria Raquel Branco (2023)
Cerebral Palsy (CP) is the most common childhood neurologic impairment. Children with CP are often prescribed ankle-foot orthoses (AFO) as an intervention meant to improve gait, but the evidence that supports its generalized use is scarce. Gait analysis is considered a gold standard in CP rehabilitation, and plantar pressure analysis can provide useful information about the way that the foot interacts with the orthoses and the ground. Plantar pressure insoles are a simple and non-invasive technology, but still an underused tool in this context. By combining the use of two rehabilitation tools (AFO and plantar pressure analysis), this PhD thesis aims to contribute to deepen the knowledge and available evidence on the field. Three separate scientific investigations were conducted: a scoping review, aiming to systematize the available evidence about the effects of different types of AFO on the gait of children with spastic bilateral cerebral palsy, showing that AFO have a positive impact in the gait of children with cerebral palsy; a test-retest reliability analysis and minimal detectable change of plantar pressure insoles in a sample of children with CP when walking in regular footwear, that determined high reliability (ICC ≥ 0.60) for 21 of the 24 parameters that were tested; and lastly a descriptive study of the plantar pressure distribution characteristics of children with cerebral palsy, while wearing plantar pressure insoles and walking with AFO, where there were positive changes in plantar pressure measurements, approximating them to the reference percentiles of typically developing children. There is a need to continue to invest in these lines of investigation, namely producing consistent evidence about the effects of AFO, unwavering prescription guidelines and producing a normative database for plantar pressure measurements in children with Cerebral Palsy.